EFFECTIVENESS OF USAGE OF SALTS AND COMPOUNDS OF MICROELEMENTS IN THE GROWTH OF LUPIN ON RADIOACTIVE CONTAMINATED SOILS - Біденко, В. М.; Кальчук, Л. А.; Трохименко, В. З. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
Leguminous crops grown in the radioactive contamination zone have the potential to accumulate radionuclides 137Cs and 90Sr to a large extent, thus contributing to radioactive contamination of livestock products, milk and meat. One of the effective methods in reducing the accumulation of radionuclides in crop production, in particular fodder, is the application of trace elements that are lacking in the Polissya area of Zhytomyr region. In addition, the trace elements contribute to increasing the yield of plants and improve their nutrition. As a result of the research in the Naroditsky district of Zhytomyr region, Polissya STOV, we found that the application of trace elements in the form of salts of trace elements Co, Cu, Zn, Mn contributed to the increase in the yield of green mass of white lupine and lupine of yellow on 2,4 and 3,6%, or on 10 and 10.7 g, of complexones of these trace elements, respectively, on 11,2 and 13,5%, or on 31,0 and 58,0 ts. Salts of trace elements contributed to a decrease in the specific activity of the green mass of lupine white by 18%, or 1.2 times, yellow lupine - by 11%, 1.2 times. Plasma complexes contributed to a decrease in the specific activity of green mass of white lupine and lupine of yellow on 24%, or in 1,3 times. Specific activity of the green mass of white lupine was high and exceeded the activity of the green mass of lupine yellow in 6.3 times, although the cultivation of cultures was carried out on the same fields, however, at different periods. White lupine was sown in the early spring, during which a considerable amount of precipitation fell during the vegetation period. Therefore, in our opinion, a significant increase in the specific activity of the green mass of white lupine was conditioned by the weather conditions. The maximum specific activity of the green mass of white lupine was 2003 Bq / kg, the minimum is 1526 Bq / kg, which is lower by 477 Bq. Reducing the specific activity of lupine is due to radio-blocking effect of micronutrient complexonates. Salts of trace elements contributed to a 1.2-fold decrease in the specific activity of the green mass of the culture.